SPESIFISITAS PARASIT PROTOZOA Trichodina sp. PADA GURAME, TAWES, NILEM DAN NILA YANG DIBUDIDAYAKAN POLIKULTUR - Utami, Prasetyarti; Rokhmani, Rokhmani (Jurnal Harpodon Borneo, 2016)
Parasites Protozoa Trichodina sp. have the ability to divide the rapid reproduction, spread wide, and can infect more than one species of fish. Fish farmers in Banyumas is still prevalent cultivate carp polyculture together with Tawes, nilem and tilapia. Research was conducted to determine the specificity of protozoan parasites Trichodina sp. certain that infects each cultivated fish in polyculture. The research method is a survey. Sampling sites in the village, Banyumas Regency Baturaden Kutasari and implementation of isolation and identification of parasites conducted at the Laboratory of Parasitology- Entomology Biology Faculty Unsoed Purwokerto. The results based on measurements of the variation morfomertrik for determination of species Trichodina sp. found on each fish is no difference or no spesifisitas. Species Trichodina sp. found in carp, Tawes, nilem and farmed tilapia polyculture is the same, Trichodina nigra, Trichodina acuta, Trichodina Trichodina nobilis and heterodentata. Keywords : Trichodina sp., Specificity, Aquaculture, polyculture